2016
DOI: 10.11604/pamj.2016.24.209.7980
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic sarcoidosis: a case series

Abstract: Sarcoidosis is a systemic non caseous granulomas disease. Liver is a common location but usually asymptomatic. Evidence based guidelines for this location treatment is lacking and the effect of corticosteroids may be inadequate. The aim of our study was to describe the clinical, biochemical, radiological and therapeutic features of seven patients with systemic sarcoidosis and liver involvement. A retrospective and descriptive monocentric study, over 3 years, including seven patients with systemic sarcoidosis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…Hyperbilirubinemia was uncommon and liver synthetic function was preserved in all patients. These observations are in line with data from previous cohort (16, 1820). ACE was elevated in only 60% of tested patients which suggest its poor sensitivity for diagnosis of hepatic sarcoidosis, similar to its poor performance for diagnosis of systemic sarcoidosis (21, 22).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Hyperbilirubinemia was uncommon and liver synthetic function was preserved in all patients. These observations are in line with data from previous cohort (16, 1820). ACE was elevated in only 60% of tested patients which suggest its poor sensitivity for diagnosis of hepatic sarcoidosis, similar to its poor performance for diagnosis of systemic sarcoidosis (21, 22).…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, liver biopsy findings of non-caseating granuloma, detected in 14 out of 16 biopsies (88%) have higher sensitivity for the diagnosis of hepatic sarcoidosis. The high sensitivity of liver biopsy has been consistently demonstrated in several cohorts (15, 16, 18). Therefore, negative imaging study does not exclude hepatic sarcoidosis, and liver biopsy should be performed if the clinical suspicion remains high.…”
Section: Discussionmentioning
confidence: 87%
“…A recent case series of 7 patients with liver sarcoidosis found that the liver was affected in the evolution of known sarcoidosis in 2 cases, while the other 5 had liver involvement at the time of diagnosis [26]. Four patients presented with upper right quadrant abdominal pain and one patient had incidentally discovered altered liver enzymes on routine evaluation.…”
Section: Clinical Aspects Of Hepatic Sarcoidosismentioning
confidence: 99%
“…Out of 289 records, 33 articles were retrieved. These included 9 review articles,8–16 2 cohort studies,17 18 and 22 case reports or series, including a total of 96 cases 19–40…”
Section: Treatmentmentioning
confidence: 99%
“…Interestingly, in most of the reported cases, biochemical abnormalities were cholestatic rather than hepatocellular 17 22 27. Ursodeoxycholic acid (UDCA) is an agent used to treat cholestasis.…”
Section: Treatmentmentioning
confidence: 99%